Compound crystal as well as preparation method and application thereof

By constructing a two-dimensional metal organic framework compound crystal with a zigzag layered structure, the efficiency problem of photocatalytic synthesis of hydrogen peroxide in the prior art under pure water and air conditions is solved, and efficient, green and safe hydrogen peroxide synthesis is achieved.

CN119707929AActive Publication Date: 2025-03-28FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311276834.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently synthesize hydrogen peroxide under pure water and air conditions, and it has problems such as high energy consumption, high hazardous waste and explosion risks.

Method used

A two-dimensional metal organic framework compound crystal with a zigzag layered structure is constructed by the liquid-liquid diffusion method. The specific chemical formula is CuX (dptz), which is rapidly prepared at room temperature and is used as a catalyst to achieve photocatalytic synthesis of hydrogen peroxide under pure water and air conditions.

Benefits of technology

It realizes the efficient photocatalytic synthesis of hydrogen peroxide under pure water and air conditions without additives, which has the advantages of green, safety and energy saving, and the preparation method is simple and fast.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707929A_ABST
    Figure CN119707929A_ABST
Patent Text Reader

Abstract

The invention discloses a compound crystal and a preparation method and application thereof, and belongs to the technical field of crystal materials. The chemical formula of the compound crystal provided by the invention is CuX (dptz); wherein X comprises Cl <->, Br <-> or I <->; and dptz is 3, 6-di-4-pyridyl-1, 2, 4, 5-tetrazine, and dptz is 3, 6-di-4-pyridyl-1, 2, 4, 5-tetrazine. The compound crystal provided by the invention has a zigzag layered structure, and can show excellent performance of photocatalytic synthesis of hydrogen peroxide under the conditions of pure water and air without any additive. The preparation method of the compound crystal provided by the invention is simple, rapid and safe, and rapid preparation of the gram-grade compound crystal can be realized at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of crystal materials, and in particular, relates to a compound crystal and a preparation method and application thereof. Background Art

[0002] At present, the industrial production of hydrogen peroxide mainly relies on the anthraquinone oxidation process, which involves four-step reactions and has many disadvantages such as high energy consumption, release of large amounts of hazardous waste and explosion risks. Under pure water and air conditions, without the need for any additives, the synthesis of hydrogen peroxide based on photocatalytic technology by reducing oxygen is an ideal method that is green, safe and energy-saving. However, at present, there is no metal-organic framework photocatalyst that can achieve efficient photocatalytic synthesis of hydrogen peroxide under pure water and air conditions without any additives. Therefore, the development of suitable catalysts is the key to promoting the advancement of this technology. Summary of the invention

[0003] In order to solve the above technical problems, the present application provides a compound crystal and a preparation method and application thereof. Through the liquid-liquid diffusion method, a series of two-dimensional metal organic frameworks with zigzag layered structures, that is, the compound crystals, are constructed. Through optimization, gram-level samples can be quickly prepared at room temperature. Under pure water and air conditions, without any additives, the obtained compound crystals can exhibit excellent photocatalytic synthesis of hydrogen peroxide performance.

[0004] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:

[0005] On the one hand, the present application provides a compound crystal having a zigzag layered structure, which can exhibit excellent photocatalytic synthesis of hydrogen peroxide performance under pure water and air conditions without any additives.

[0006] A compound crystal, wherein the chemical formula of the compound crystal is CuX(dptz);

[0007] Among them, X includes Cl - Br - or I - ;

[0008] dptz is 3,6-di-4-pyridyl-1,2,4,5-tetrazine.

[0009] The structural formula of dptz described in this application is as follows:

[0010]

[0011] Optionally, the CuX(dptz) comprises Cu + 、μ2-X - and dptz ligands;

[0012] Among them, each Cu + With two μ2-X - , the two pyridine N atoms on the two dptz ligands coordinate to form a distorted tetrahedral configuration;

[0013] Every two Cu + By a μ2-X - Bridge to form an infinitely extended one-dimensional neutral (CuX)∞ chain;

[0014] Two adjacent one-dimensional neutral (CuX)∞ chains are connected by dptz ligands as connectors to construct a two-dimensional zigzag network.

[0015] Optionally, the CuX(dptz) displays an AA stacking pattern or an ABAB stacking pattern in space;

[0016] The space group of the CuX(dptz) is P2 / c, P21 / c or Pccn.

[0017] Optionally, the unit cell parameters of the compound crystal are:

[0018] α=γ=90°, β=90°~94.3°, Z=2~4.

[0019] On the second aspect, the present application provides a method for preparing the above-mentioned compound crystals. Through the liquid-liquid diffusion method, a series of two-dimensional metal-organic frameworks with zigzag layered structures are constructed. Through optimization, the rapid preparation of gram-level compound crystals can be achieved at room temperature.

[0020] The method for preparing the above compound crystals comprises the following steps:

[0021] CuX, dptz and a solvent are mixed and allowed to stand to obtain crystals of the compound.

[0022] Optionally, the mass ratio of CuX to dptz is 1:0.1-2.

[0023] Optionally, the mass ratio of CuX to dptz is independently selected from any value of 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, or any range between the two.

[0024] Optionally, the step of washing, centrifuging and drying is sequentially included after the standing.

[0025] Optionally, the component used for washing is acetonitrile.

[0026] Optionally, the centrifugal speed is 7000-9000 rpm;

[0027] The centrifugation time is 0.5 to 1.5 min.

[0028] Optionally, the centrifugal rotation speed is independently selected from any value among 7000 rpm, 7500 rpm, 8000 rpm, 8500 rpm, 9000 rpm or any range between the two.

[0029] Optionally, the centrifugation time is independently selected from any value among 0.5 min, 0.8 min, 1 min, 1.2 min, 1.5 min, or any range between the two.

[0030] Optionally, the drying temperature is 70-90°C;

[0031] The drying time is 10 to 15 hours.

[0032] Optionally, the drying temperature is independently selected from any value among 70°C, 75°C, 80°C, 85°C, 90°C or any range therebetween.

[0033] Optionally, the drying time is independently selected from any value among 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, or any range between two of them.

[0034] Optionally, the mixing includes mixing I and mixing II.

[0035] Optionally, when the mixing is mixing I, the solvent includes acetonitrile and dichloromethane.

[0036] Optionally, when the mixing is mixing I, the standing time is 10 to 15 days.

[0037] Optionally, when the mixing is mixing I, the standing time is independently selected from any value among 10d, 11d, 12d, 13d, 14d, 15d or a range value between any two of them.

[0038] Optionally, when the mixing is mixing I, a buffer solution needs to be added during the mixing process.

[0039] Optionally, the buffer comprises acetonitrile and dichloromethane.

[0040] Optionally, when the mixing is mixing II, the solvent includes acetonitrile.

[0041] Optionally, the mixing II is performed under ultrasonic conditions;

[0042] The power of the ultrasound is 200-400W;

[0043] The ultrasonic time is 0.5 to 1.5 minutes.

[0044] Optionally, the ultrasound time is independently selected from any value among 0.5 min, 0.8 min, 1 min, 1.2 min, 1.5 min, or any range between two values.

[0045] Optionally, when the mixing is mixing II, the standing time is 5 to 15 minutes.

[0046] Optionally, when the mixing is mixing II, the standing time is independently selected from any value among 5 min, 8 min, 10 min, 12 min, 15 min, or any range between two of them.

[0047] In a third aspect, the present application provides the use of the above compound crystals as a catalyst.

[0048] In a fourth aspect, the present application provides the use of the above compound crystals in the photocatalytic synthesis of hydrogen peroxide.

[0049] Compared with the prior art, this application has the following beneficial effects:

[0050] (1) The compound crystals provided in the present application have a zigzag layered structure and can exhibit excellent photocatalytic performance in synthesizing hydrogen peroxide in pure water and air without any additives.

[0051] (2) The method for preparing compound crystals provided in the present application is simple, rapid, and safe, and can achieve rapid preparation of gram-level compound crystals at room temperature.

[0052] (3) The compound crystals provided in this application can be used as catalysts in the field of photocatalytic synthesis of hydrogen peroxide, and have the advantages of being green, safe and energy-saving. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 This is the asymmetric unit structure diagram of CuBr-dptz of this application;

[0055] Figure 2 For this application, CuBr-dptz + The coordination environment structure diagram of

[0056] Figure 3Schematic diagram of the structure of CuBr-dptz of the present application observed along the a-axis;

[0057] Figure 4 A schematic diagram of the structure of CuBr-dptz of the present application observed along the b-axis;

[0058] Figure 5 Thermogravimetric diagram of CuX-dptz for this application;

[0059] Figure 6 This is the powder X-ray diffraction analysis and water stability comparison chart of CuCl-dptz in this application;

[0060] Figure 7 Powder X-ray diffraction analysis and water stability comparison of CuBr-dptz for this application;

[0061] Figure 8 Powder X-ray diffraction analysis and water stability comparison of CuI-dptz for this application;

[0062] Fig. 9 is the photocatalytic hydrogen peroxide yield under different CuBr-dptz dosages;

[0063] Fig.10 The relationship between the concentration and time of hydrogen peroxide synthesis by CuX-dptz photocatalyst of this application series;

[0064] Fig.11 The results of four repeated photocatalytic synthesis of hydrogen peroxide experiments using CuBr-dptz as catalyst in this application;

[0065] Fig.12 This is the result of a long-term photocatalytic synthesis of hydrogen peroxide experiment using CuBr-dptz as a catalyst. DETAILED DESCRIPTION

[0066] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0067] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0068] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.

[0069] Example 1

[0070] Preparation of CuX(dptz) (also known as CuX-dptz) by liquid-liquid diffusion method:

[0071] Dissolve 2mg CuX (CuCl, CuBr, CuI) in 2mL acetonitrile to obtain solution A, and dissolve 2mg dptz in 2mL dichloromethane to obtain solution B. Take a test tube, add solution B as the lower layer at the bottom of the test tube, then add 10mL of buffer (acetonitrile: dichloromethane = 1:1, volume ratio) as the middle layer, and finally add solution A as the upper layer. After two weeks, dark purple block crystals with a size of about 100μm were collected. Wash with 3mL acetonitrile, centrifuge at 8000rpm for 1 minute, and the obtained solid sample is dried in a vacuum oven at 80℃ for 12 hours. After drying, the masses of CuCl-dptz, CuBr-dptz and CuI-dptz are 0.3mg, 0.35mg and 0.5mg respectively, and the yields based on dptz ligands are 11.5%, 11.2% and 14.7% respectively.

[0072] Example 2

[0073] Preparation of CuX(dptz) (also known as CuX-dptz) by rapid synthesis:

[0074] 2mg CuX (CuCl, CuBr, CuI) was dissolved in 2mL acetonitrile to obtain liquid A, 2mg dptz was dissolved in 2mL acetonitrile to obtain liquid B, and liquid A and liquid B were directly mixed under ultrasonic conditions. After 10 minutes, 3mL acetonitrile was used for washing, and the solid sample was centrifuged at 8000rpm for 1 minute. The obtained solid sample was dried in a vacuum oven at 80℃ for 12 hours to obtain a dark purple powder sample with a size of about 400nm. After drying, the masses of CuCl-dptz, CuBr-dptz and CuI-dptz were 2.42mg, 2.64mg and 3.06mg, respectively, and the yields based on the dptz ligand were 90.3%, 86.7% and 89.7%, respectively.

[0075] Example 3

[0076] Gram-scale preparation of CuX(dptz) (i.e. CuX-dptz):

[0077] The reaction raw materials in the above-mentioned embodiment 2 were proportionally expanded 400 times, that is, CuX (800 mg) and dptz (800 mg) were dissolved in 800 mL of acetonitrile, and then directly mixed under ultrasonic conditions, which can achieve gram-level preparation. After 10 minutes, 3 mL of acetonitrile was washed, centrifuged at 8000 rpm for 1 minute, and the obtained solid sample was dried in a vacuum drying oven at 80 ° C for 12 hours to obtain a dark purple powder sample with a size of about 400 nm. After drying, the masses of CuCl-dptz, CuBr-dptz and CuI-dptz were 1.019.5 g, 1.0955 g and 1.2817 g, respectively, and the yields based on the dptz ligand were 89.8%, 85.2% and 88.7%, respectively.

[0078] Experimental Example 1

[0079] Taking the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in Example 1 as examples, their structural characteristics were observed and it was found that CuCl-dptz, CuBr-dptz and CuI-dptz crystallized in monoclinic space groups P2 / c, P21 / c and orthorhombic space groups Pccn, respectively. The relevant parameters are shown in Tables 1 to 7. The asymmetric unit structure of CuBr-dptz is shown in Figure 1 CuBr-dptz + The coordination environment structure diagram is as follows Figure 2 The schematic diagram of the structure of CuBr-dptz in the present application is shown along the a-axis. Figure 3 The schematic diagram of the structure of CuBr-dptz in the present application is shown along the b axis. Figure 4 shown.

[0080] Table 1 Crystal structure data of CuX-dptz

[0081]

[0082]

[0083] (Note: The numbers in brackets in this application form represent the error value of one thousandth, such as 3.7590(3) means 3.7590±0.003, the same below)

[0084] Table 2 Bond length data of CuCl-dptz

[0085]

[0086] 1 1+X,+Y,+Z; 2 1-X,+Y,3 / 2-Z; 3 1-X,-Y,1-Z

[0087] Table 3 Bond angle data of CuCl-dptz

[0088]

[0089]

[0090] 1 1+X,+Y,+Z; 2 1-X,+Y,3 / 2-Z; 3 -1+X,+Y,+Z; 4 1-X,-Y,1-Z Table 4 Bond length data of CuBr-dptz

[0091]

[0092] 1 1+X,+Y,+Z; 2 -X,1-Y,1-Z; 3 1-X, 1-Y, 2-Z

[0093] Table 5 Bond angle data of CuBr-dptz

[0094]

[0095]

[0096] 1 1+X,+Y,+Z; 2 -1+X,+Y,+Z; 3 -X,1-Y,1-Z; 4 1-X, 1-Y, 2-Z Table 6 Bond length data of CuI-dptz

[0097]

[0098] 1 1+X,+Y,+Z; 2 1 / 2-X, 3 / 2-Y, +Z; 3 1-X, 1-Y, 1-Z

[0099] Table 7 Bond angle data of CuI-dptz

[0100] atom atom atom Bond angle / ° atom atom atom Bond angle / ° <![CDATA[Cu1 1 ]]> I1 Cu1 105.68(3) N3 C6 C3 118.0(4) I1 Cu1 <![CDATA[I1 2 ]]> 105.68(3) N2 C6 C3 117.3(4) <![CDATA[N1 3 ]]> Cu1 I1 114.18(9) <![CDATA[N2 4 ]]> N3 C6 118.2(4) N1 Cu1 I1 107.93(9) N1 C5 C4 124.2(4) <![CDATA[N1 3 ]]> Cu1 <![CDATA[I1 2 ]]> 107.93(9) C5 C4 C3 118.4(4) N1 Cu1 <![CDATA[I1 2 ]]> 114.18(9) <![CDATA[N3 4 ]]> N2 C6 117.2(4) N1 Cu1 <![CDATA[N1 3 ]]> 107.13(19) N1 C1 C2 122.5(4) C5 N1 Cu1 120.0(3) C1 C2 C3 119.7(4) C5 N1 C1 117.3(3) C4 C3 C6 120.0(4) C1 N1 Cu1 122.5(3) C2 C3 C6 122.1(4) N3 C6 N2 124.7(4) C2 C3 C4 117.8(4)

[0101] 1 1+X,+Y,+Z; 2 -1+X,+Y,+Z; 3 1 / 2-X, 3 / 2-Y, +Z; 4 1-X, 1-Y, 1-Z

[0102] Combination Figure 1 to Figure 4 , Tables 1 to 7 show that, taking CuBr-dptz as an example, its asymmetric unit consists of two half dptz ligands at different positions, a Cu + ions and a μ2-Br - Ion composition. Each Cu + ions and two μ2-Br - The ion is coordinated with the two pyridinic N atoms of the two dptz ligands to form a distorted tetrahedral configuration. + The ion consists of a μ2-Br - Ion bridging forms an infinitely extended one-dimensional neutral (CuBr)∞ chain, in which there are two types of Cu-Br bonds with lengths of and The dptz ligand acts as a linker to connect adjacent one-dimensional neutral (CuBr)∞ chains to construct a two-dimensional zigzag network. Observed along the a-axis, the dihedral angle formed by the two pyridine rings coordinated to the same copper is 71.472°. The thickness of the CuBr-dptz monolayer structure is about The interlayer distance is approximately With Cl - Br - and I - The structures of the three compounds show regular changes as the atomic radius increases. Specifically, the length of the Cu-X bond becomes longer, the dihedral angle reflecting the degree of fluctuation becomes larger, the monolayer gradually becomes thicker, and the interlayer spacing gradually becomes wider. In space, CuCl-dptz shows an AA stacking pattern, while CuBr-dptz and CuI-dptz both show an ABAB stacking pattern.

[0103] Experimental Example 2

[0104] Taking the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in Example 2 as examples, thermogravimetric analysis was performed on them.

[0105] The results are as follows Figure 5 As shown. Figure 5 It can be seen that the structures of CuCl-dptz, CuBr-dptz and CuI-dptz can be stable up to 270°C.

[0106] Experimental Example 3

[0107] Taking the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in Example 2 as examples, powder X-ray diffraction analysis and water stability were performed:

[0108] The comparison of the theoretical graph obtained by fitting the single crystal data of the complex sample with the X-ray powder diffraction results of the actual fresh sample and the sample after being immersed in water for 10 days is shown as follows: Figure 6 , Figure 7 , Figure 8 As shown. Figure 6 , Figure 7 , Figure 8 It can be seen that the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in the present application are samples with high crystallinity and high purity, and their structures remain stable after being immersed in water for 10 days, showing good stability.

[0109] Experimental Example 4

[0110] Taking the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in Example 2 as examples, the photocatalytic synthesis of hydrogen peroxide performance was tested. Under pure water and air conditions, without the need for any additives, the series of CuX-dptz complexes achieved photocatalytic synthesis of hydrogen peroxide.

[0111] Taking CuBr-dptz as an example, an optimization experiment was conducted, such as Fig. 9 As shown in the figure, as the amount of photocatalyst increases, the yield of hydrogen peroxide decreases. When 5 mg CuBr-dptz is used as the photocatalyst, it has the highest hydrogen peroxide production rate. The optimized photocatalytic conditions are as follows: 5 mg photocatalyst, 80 mL water, 300 W xenon lamp (equipped with 400 nm filter). Subsequent photocatalytic experiments were carried out under this condition.

[0112] Fig.10 The relationship between the concentration and time of the CuX-dptz photocatalyst for the synthesis of hydrogen peroxide. Fig.10 It can be seen that after 60 minutes of illumination, the hydrogen peroxide concentrations in the system reached 71.5, 149.3, and 47.2 μM, respectively, with corresponding hydrogen peroxide generation rates of 906.6, 1864.9, and 676.5 μmol g - 1 h -1 .

[0113] Fig.11 The results of four repeated experiments on the photocatalytic synthesis of hydrogen peroxide using CuBr-dptz as the catalyst. The results of four repeated experiments show that the rate of photocatalytic synthesis of hydrogen peroxide by CuBr-dptz remains within a stable fluctuation range.

[0114] Fig.12The results of a long-term photocatalytic synthesis of hydrogen peroxide using CuBr-dptz as a catalyst. The results show that in the 12-hour photocatalytic experiment, the accumulated concentration of hydrogen peroxide in the system reached 308.02μM.

[0115] Experimental Example 5

[0116] Under the conditions of pure water, air, and without any additives, the performance of the CuCl-dptz, CuBr-dptz, and CuI-dptz prepared in Example 2 of the present application in photocatalytic synthesis of hydrogen peroxide was compared with that of other materials. The results are shown in Table 8.

[0117] Table 8 Performance comparison of photocatalytic synthesis of hydrogen peroxide by different materials

[0118]

[0119] It can be seen from Table 8 that compared with other photocatalytic materials, the CuCl-dptz, CuBr-dptz and CuI-dptz prepared in the present application have better catalytic performance and higher hydrogen peroxide yield.

[0120] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A compound crystal, characterized in that: The chemical formula of the compound crystal is CuX(dptz); Among them, X includes Cl - Br - or I - ; dptz is 3,6-di-4-pyridyl-1,2,4,5-tetrazine.

2. A compound crystal according to claim 1, characterized in that: The CuX(dptz) comprises Cu + 、μ2-X - and dptz ligands; Among them, each Cu + With two μ2-X - , the two pyridine N atoms on the two dptz ligands coordinate to form a distorted tetrahedral configuration; Every two Cu + By a μ2-X - Bridge to form an infinitely extended one-dimensional neutral (CuX)∞ chain; Two adjacent one-dimensional neutral (CuX)∞ chains are connected by dptz ligands as connectors to construct a two-dimensional zigzag network.

3. A compound crystal according to claim 1, characterized in that: The CuX(dptz) exhibits an AA stacking mode or an ABAB stacking mode in space; The space group of the CuX(dptz) is P2 / c, P21 / c or Pccn.

4. A compound crystal according to claim 1, characterized in that: The unit cell parameters of the compound crystal are: α=γ=90°, β=90°~94.3°, Z=2~4.

5. The method for preparing a compound crystal according to any one of claims 1 to 4, characterized in that: The steps include: CuX, dptz and a solvent are mixed and allowed to stand to obtain crystals of the compound.

6. The method for preparing a compound crystal according to claim 5, characterized in that: The mass ratio of CuX to dptz is 1:0.1-2; Preferably, the step of washing, centrifuging and drying is sequentially included after the standing. Preferably, the component used for washing is acetonitrile; Preferably, the centrifugal speed is 7000-9000 rpm; The centrifugation time is 0.5 to 1.5 min; Preferably, the drying temperature is 70-90°C; The drying time is 10 to 15 hours.

7. The method for preparing a compound crystal according to claim 5, characterized in that: The mixing includes mixing I and mixing II; Preferably, when the mixing is mixing I, the solvent comprises acetonitrile and dichloromethane; Preferably, when the mixing is mixing I, the standing time is 10 to 15 days; Preferably, when the mixing is mixing I, a buffer solution needs to be added during the mixing process; Preferably, the buffer comprises acetonitrile and dichloromethane.

8. The method for preparing a compound crystal according to claim 7, characterized in that: When the mixture is mixture II, the solvent includes acetonitrile; Preferably, the mixing II is carried out under ultrasonic conditions; The power of the ultrasound is 200-400W; The ultrasonic time is 0.5 to 1.5 minutes; Preferably, when the mixing is mixing II, the standing time is 5 to 15 minutes.

9. Use of the compound crystal according to any one of claims 1 to 4 as a catalyst.

10. Use of the compound crystal according to any one of claims 1 to 4 in photocatalytic synthesis of hydrogen peroxide.

Citation Information

Patent Citations

  • Inorganic-organic hybrid compound crystal K10Cu9I7L12. XH2O as well as preparation method and application thereof

    CN114716461A

  • Series of five-coordinate copper complex crystal materials and preparation method and application thereof

    CN116554209A